Writing Assessment: Use of Analytical Rubrics to Assess Essay Writing –Case of Third Year LMD Students of Biskra University - Saihi, Hanane (Sciences humaines, 2014)
This work presents the benefits of using rubrics to develop students writing process, and to help the evaluator to enhance both writing assessment and instruction. In a group of 20 undergraduate students, an assignment to write an essay was set followed by rubrics to recognize those students’ weaknesses to write an essay. These rubrics clearly served in rethinking the classroom instruction and assessment of writing. They help to integrate certain procedures in the teaching of essay writing on part of the instructor in a formative classroom assessment.  On part of the students, they serve them to enact a student-centered assessment that picture their weaknesses as well as their strengths. The use of rubrics enables both the instructor and the student to improve the writing performance. Key words: assessment rubrics, essay writing, process genre based approach, formative assessment, student-centered assessment